Elektabilitas Gaya Kepemimpinan Perusahaan Kertas di Tangerang - Gina Majesta (Warta Pendidikan | e-Journal, 2021)
This study aims to determine the ability of leadership style applied in PT CPK influence its employees. This study uses a type of qualitative research method with data collection techniques carried out by triangulation (combined). The results of this study are that the leadership style applied by the leaders at PT CPK is the Authoritarian Leadership Style. Advice from the author is that leaders often meet face-to-face with employees and communicate, so that the work environment becomes more comfortable and work pressure decreases.